Factors affecting information systems success - Whyte, Grafton; Bytheway, Andrew (Cranfield University, 1995)
There is continuing difficulty in achieving success with information systems, particularly in the sense of meeting users’ needs and expectations. This suggests that a fresh examination of the issues is needed in order that we understand better the causes of success and failure. Much previous research in this area has adopted one of two perspectives: improving the processes of systems development, or the structure and content of systems products. This approach has had only limited success in dealing with the problem. A wider review of existing research literature suggests that, in addition to the process and product viewpoint, an important factor in achieving success in the general case is the service management viewpoint. The question therefore arises: is service important in the provision of information systems, and is it a factor in achieving success in the eyes of the users? It is possible that service components exist which are unrecognised by those managing the development and use of information systems. If these components can be identified and understood, then they can be used to improve the overall level of success achieved. By applying repertory grid techniques a total of 43 constructs have been found which relate to user’s perceptions of success with information systems in business. Further analysis reduces these to 21 attributes which provide the basis of a new assessment and measurement framework. The use of these attributes in practice is illustrated using two cases: an information service provider and a hospital equipment supplier. Early experience suggests that software houses, commercial organisations and information systems departments can use these attributes as a management tool, and thereby improve the level of service and business benefit that they deliver to their customers.
Keywords: Information systems success; Service management; Service management; User perceptions of success; Repertory grid